2015
DOI: 10.4186/ej.2015.19.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Kanban System for Rubber Seals Production

Abstract: Abstract.A key success for automotive suppliers relies on its on-time delivery and efficient manufacturing process. A case-study rubber seal manufacturer is using just in time (JIT) techniques, requiring efficient process flow with low wastes. However, the majority of the current processes still rely on workers' expertise that can lead to process errors. In 2011, 699 events of rubber supplying delays were found and 525 events or 75.11% of these delays are due to inappropriate ordering and management of the Kan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Even individual implementation of Lean and Industry 4.0 is challenging, and the integrated implementation is even more so. For Industry 4.0, a survey including over 1,000 manufacturing companies showed that only 14% of smart manufacturing initiatives were successful in 2019 (Petit, Brosset and Bagnon, 2019). For Lean, a failure rate of 60-90% has been observed over the years (Pearce, Pons and Neitzert, 2018, Dora, Kumar, Van Goubergen, Molnar, Gellynck, 2013, Dora & Gellynck, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Even individual implementation of Lean and Industry 4.0 is challenging, and the integrated implementation is even more so. For Industry 4.0, a survey including over 1,000 manufacturing companies showed that only 14% of smart manufacturing initiatives were successful in 2019 (Petit, Brosset and Bagnon, 2019). For Lean, a failure rate of 60-90% has been observed over the years (Pearce, Pons and Neitzert, 2018, Dora, Kumar, Van Goubergen, Molnar, Gellynck, 2013, Dora & Gellynck, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], the goal was to reduce the number of delays in supply of rubbers. The number of rubber supplying delays is reduced from 86 events to 12 events.…”
Section: Literature Surveymentioning
confidence: 99%
“…The Japanese word Kanban, which translates to 'shield' is synonymous with de-mand planning. Kanban has its roots in the early days of the Toyota production system [1]. In the late 1940s, Taiichi Onho developed Kanbans to control inter-process production and implement just-in-time (JIT) manufacturing at Toyota's manufacturing facilities in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the station C, when the welder take away the components in the buffer at a time, the pull effect is created [40]. It is feasible for the E-kanban system to be set on the station in the upstream.…”
Section: Figure 6 Components Process Diagrammentioning
confidence: 99%